2021
DOI: 10.1111/1440-1630.12729
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory discrimination impairment in children with hemiplegic cerebral palsy as measured by the sense_assess© kids

Abstract: Cerebral palsy (CP) is an umbrella term for an injury or malformation in the developing infant brain resulting in limitations in motor function and disturbances to sensation, perception, cognition, communication and behaviour (Rosenbaum et al., 2007). Limitations in motor function affecting primarily one side of the body is termed hemiplegia and is the most frequently occurring distribution of motor impairment in children with CP (Stanley et al., 2000). Impairments in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Beyond their motor problems, at least 80 percent of children with uCP present with additional somatosensory or visual impairments. 23,25,26 Moreover, it is well-known that sensory input is a key cornerstone for planning and netuning motor actions. 27,28 Indeed, previous studies have already reported on the relation between increased somatosensory de cits and reduced bimanual function in children with uCP.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond their motor problems, at least 80 percent of children with uCP present with additional somatosensory or visual impairments. 23,25,26 Moreover, it is well-known that sensory input is a key cornerstone for planning and netuning motor actions. 27,28 Indeed, previous studies have already reported on the relation between increased somatosensory de cits and reduced bimanual function in children with uCP.…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study showing sensory deficits in the upper extremity across the cohort of adults with CP and a spastic diplegic presentation were somewhat surprising given that those with diplegia are assumed to exclusively have lower extremity impairments. This may be due to the strength of the WPST to distinguish deficits in position sense in clinical populations ( 42 , 68 , 69 ), but also may reflect an inadequate clinical picture of those with a diplegic presentation. The current findings indicate that hand proprioceptive acuity is diminished in adults with CP, building on past studies that have revealed similar deficits across the lifespan ( 13 15 , 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of studies related to proprioception in this population remains very low (11). Further investigation of the source and timing of these sensory deficits in people with CP may reveal effective targets for therapeutic intervention, as suggested in prior studies (15,69,70). The relationship of these sensory deficits to the extent of the upper extremity motor control challenges in individuals with CP across the lifespan remains an important area for further study.…”
Section: Sensory Function In Adults With Cpmentioning
confidence: 99%
“…Children and adolescents with uCP present with motor and somatosensory impairments predominantly at one side of the body, which are often more pronounced in the upper compared to the lower limb [9]. Although CP has been primarily defined as a motor disorder, previous research has shown that up to 90% of the children and adolescents with uCP also present with impairments in one or more modalities of somatosensation [10][11][12].…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%